Social Communication in a Community: The Bridge among Generations - Leliūgienė, Irena; Kaušylienė, Angelė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Referring to scientific literature, the article aims to define criteria of social communication, which are identified by socio-cultural, psychological, communication competences that in value viewpoint are essential for partnership relations among generations. The article presents network characteristics of successful partnership among generations. On the basis of theoretical works‘ analysis the research methodology as well as quantitative and qualitative research instrument, which allowed performing the empirical research, has been designed. The article also presents essential results of the research: how social communication and partnership networks create premises for bridges among generations in a community. The research has been performed  in N community in Lithuania‘s second largest city. In this article the authors pursue to find the answer to the problematic question – what experience of communities‘ creation of bridges between social communication and partnership networks can strengthen bridges among generations.